Atomic diffusion behavior near the bond interface during the explosive welding process based on molecular dynamics simulations. (June 2022) - Ma, Yong; Zhang, Song; Wang, Tao; He, Yao; Chen, Wenlin; Liu, Lanjun; Liu, Fei
Abstract: Based on the Hastelloy/stainless steel explosive-welded composite (the main elements are Ni and Fe respectively), this work investigated the diffusion behavior of main elements near the bond interface during the explosive welding process through molecular dynamics simulations and experiments. According to the characteristics of temperature and pressure of explosive welding process, the simulation of explosive welding process is classified into three stages, namely loading stage, unloading stage, and cooling stage. The diffusion behavior of the main elements (Ni and Fe) near the interface was investigated by two methods. The first one is to calculate the mean square displacement of the main elements. And the second one is to compare the system configurations and the results of radial distribution function at different stages. In the simulation, the thickness of the diffusion layer of the Vpx (the transverse velocity)= 0.2 km/s, Vpx = 0.4 km/s, Vpx = 0.6 km/s, Vpx = 0.8 km/s weldments are about 14, 20, 49, and 61 Å. The results show that the atomic diffusion near the interface mainly occurs in the unloading stage and the beginning of the cooling stage. Only when the melting occurs during these stages, the atoms of the bonding interface can diffuse obviously. In this experiment, the thicknesses of the diffusion layer at the wave peak and the vortex zone are about 20 µm and 230 µm respectively. This conclusion is verified by the results of experimental investigations and the references. Also, the diffusion layer thickness with the increasing the absolute value of Vpz (the longitudinal velocity) and Vpx, and the absolute value of Vpz can make a greater contribution to the thickness of the diffusion layer than that of Vpx . The thickness of the diffusion layer at the interface will be significantly increased if the melting occurred during the welding process. Graphical Abstract: ga1 Highlights: The atomic diffusion at the interface of each stage of explosive welding is studied. In explosive welding, atomic diffusion will occur at the interface atoms. Increasing the absolute value of Vpz will improve the thickness of the diffusion layer.